29.9k views
1 vote
Expand.
If necessary, combine like terms.
(2+7x)(2-7x)
stuck? Watch a vide​

User Ian Boyd
by
6.6k points

2 Answers

5 votes

Answer:


\boxed{\bold{-49x^2+4}}

Step-by-step explanation:

Apply Difference of Two Squares Formula:
\bold{\left(a+b\right)\left(a-b\right)=a^2-b^2}


\bold{a=2,\:b=7x}

=
\bold{2^2-\left(7x\right)^2}

Simplify
\bold{2^2-\left(7x\right)^2: \ -49x^2+4}


\boxed{\bold{-49x^2+4}}

User Jonatascsilva
by
5.9k points
2 votes

Answer:4-49x^2

Step-by-step explanation:

2^2-(7x)^2= given ans

User Alex Stuckey
by
5.7k points